How effective are face masks in operation theatre? A time frame analysis and recommendations. - Kelkar, Uday Siddharaj; Gogate, Bageshri; Kurpad, Satish; Gogate, Parikshit; Deshpande, Madan (International Journal of Infection Control, 2013)
Study was conducted to check the efficacy of face masks in limiting bacterial dispersal when worn continuously in Operation Theater. A comparison was done to find out difference between fabric and two ply disposable masks. Prior to wearing the mask first sample was collected using cough plate method holding a blood agar plate approximately 10 - 12 centimeters away from the mouth. The personnel were asked to produce “ahh” phonation. Participants were then asked to don the face mask, continue routine work and report to the study center located inside the theater for further sample collections at designated intervals of 30, 60, 90, 120 and 150 minutes after wearing the two ply disposable mask. The study was replicated on immediate next day using fabric mask made of cotton keeping all the other conditions and personnel exactly the same. Bacterial counts before wearing the mask were 5.36+4.38 and 5.7+2.99 on day 1 and day 2 of study. Bacterial counts were 0.96+1.06 (P<0.001) and 0.7+0.87 (P=0) at 30 min; 2.33+1.42 (P<0.001) and 2.36+1.03 (P=0) at 60 min; 3.23+1.54 (P=0.007) and 4.16+1.78 (P=0.011) at 90 min; 5.63+4.02 (P=0.67) and 4.9+1.98 (P=0.161) at 120 min and 7.03+4.45 (P=0.019) and 5.6+2.21 (P=0.951) at150min respectively for fabric and two ply disposable mask. Counts were near pre-wear level in about two hours irrespective of the type of mask. There was no significant difference between cotton fabric and two ply disposable masks. Face masks significantly decreased bacterial dispersal initially but became almost ineffective after two hours of use. Key words: Face mask, Fabric, Disposable, nosocomial infection, bacterial count.